Les stéréotypes de la femme dans la caricature de Dilem Ali - Sonia Benamsili (Corela)
The caricature of Ali Dilem is inspired from traditional representations and stereotypes. It feeds on forms already known to quickly communicate her message and to be understood by the largest number of readers. Among these stereotypes, women's one is the most used. Indeed, she is represented in different ways, and attached to many themes. Therefore, women are a perfect area of investigation to see how they are used in Dilem's caricatures, to deepen the concept of stereotype, to show the importance of their presence in the caricature and the caricaturist use of various manipulations to produce his drawings in order to achieve his objectives. In other words, we will see how women are represented in the caricatures and we will clarify Dilem's objectives through this use.